Role of the LytSR Two-Component Regulatory System in Staphylococcus lugdunensis Biofilm Formation and Pathogenesis - Dahyot, Sandrine; Oxaran, Virginie; Niepceron, Maïté; Dupart, Eddy; Legris, Stéphanie; Destruel, Laurie; Didi, Jennifer; Clamens, Thomas; Lesouhaitier, Olivier; Zerdoumi, Yasmine; Flaman, Jean-Michel; Pestel-Caron, Martine (Frontiers in Microbiology, 2020)
Staphylococcus lugdunensis is a coagulase negative Staphylococcus, recognized as a virulent pathogen. It is responsible for a wide variety of infections, some of which are associated with biofilm production, such as implanted medical device infections or endocarditis. However, little is known about S. lugdunensis regulation of virulence factor expression. Two-component regulatory systems (TCS) play a critical role in bacterial adaptation, survival and virulence. Among them, LytSR is widely conserved, but has variable roles in different organisms, all connected to metabolism or cell death and lysis occurring during biofilm development. Therefore, we investigated here the functions of LytSR in S. lugdunensis pathogenesis. Deletion of lytSR in S. lugdunensis DSM 4804 strain did not alter either susceptibility to Triton X-100 induced autolysis or death induced by antibiotics targeting cell wall synthesis. Interestingly, ΔlytSR biofilm was characterized by a lower biomass, a lack of tower structures and a higher rate of dead cells compared to the wild-type strain. Virulence towards Caenorhabditis elegans using a slow-killing assay was significantly reduced for the mutant compared to the wild-type strain. In contrast, the deletion of lytSR had no effect on the cytotoxicity of S. lugdunensis towards the human keratinocyte cell line HaCaT. Transcriptional analyses conducted at mid- and late-exponential phases showed that lytSR deletion affected the expression of 286 genes. Most of them were involved in basic functions such as the metabolism of amino acids, carbohydrates and nucleotides. Furthermore, LytSR appeared to be involved in the regulation of genes encoding known or putative virulence and colonization factors, including the fibrinogen-binding protein Fbl, the major autolysin AtlL and the type VII secretion system. Overall, our data suggest that the LytSR TCS is implicated in S. lugdunensis pathogenesis, through its involvement in biofilm formation and potentially by the control of genes encoding putative virulence factors.